FREQUENCY OF ANTI-TUBERCULOUS THERAPY-INDUCED HEPATOTOXICITY IN PATIENTS AND THEIR OUTCOME - Tariq, Sumbal; Khan, Tahir Saleem; Malik, Saqib; Anwar, M. Shamim; Rashid, Abdul (Journal of Ayub Medical College Abbottabad, 2009)
Background: Tuberculosis (TB) is a very common droplet infection especially in the northern areas. If untreated, the disease may be fatal within 5 years in more than half of cases. To study the frequency of anti-tuberculous therapy (ATT) induced hepato-toxicity was the subject of the present hospital based descriptive study. Method: The study was conducted in Medical Unit, Ayub Teaching Hospital and patients with diagnosed Tuberculosis in whom ATT was initiated were included in the study. The subsequent development of elevated liver enzyme levels and hepatitis, amongst some members of the study group; was diagnosed, with the help of clinical findings and Liver Function Tests (LFT’s) and were dealt with according to severity. Results: Out of the 500 patients studied 277 (55.4%) were male and 223 (44.6%) were female, 203 (40.5%) were in age group 21-35 years, 136 (27.1%) in age group 36-50 years, 141 (28.1%) in age group 51-65 years while 20 (4%) were above 65 years of age. Out of them 40 (8%) developed hepatotoxicity, 21 (4.2%) patients amongst the study group developed overt hepatitis, 20 (4%) of them made an uneventful recovery while 1 (0.2%) died of Fulminant Hepatic Failure (FHF). Conclusions: ATT-induced hepato-toxicity, was frequently encountered in patients put on ATT. Keywords: Tuberculosis (TB), Anti-Tuberculous Therapy (ATT), Fulminant Hepatic Failure (FHF), Multi Drug Resistant (MDR), Liver Function Tests (LFT’s).